Pyroptosis: Role and Mechanisms in Cardiovascular Disease - Chen, Xinzhe; Tian, Peng-Chao; Wang, Kai; Wang, Man; Wang, Kun (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is a common disease that poses a huge threat to human health. Irreversible cardiac damage due to cardiomyocyte death and lack of regenerative capacity under stressful conditions, ultimately leading to impaired cardiac function, is the leading cause of death worldwide. The regulation of cardiomyocyte death plays a crucial role in CVD. Previous studies have shown that the modes of cardiomyocyte death include apoptosis and necrosis. However, another new form of death, pyroptosis, plays an important role in CVD pathogenesis. Pyroptosis induces the amplification of inflammatory response, increases myocardial infarct size, and accelerates the occurrence of cardiovascular disease, and the control of cardiomyocyte pyroptosis holds great promise for the treatment of cardiovascular disease. In this paper, we summarized the characteristics, occurrence and regulation mechanism of pyroptosis are reviewed, and also disscuessed its role and mechainsms in CVD, such as atherosclerosis (AS), myocardial infarction (MI), arrhythmia and cardiac hypertrophy.